Analytical solutions for the dynamic analysis of a modular floating structure for urban expansion - Wang, Shengzhe (Ocean engineering, 2022)
Modular floating structures (MFS) offer a sustainable alternative over traditional land reclamation for the expansion of coastal megalopolises in the context of climate change adaptation. Yet, there are currently no guidelines for structural engineers pertaining to their analysis and design. This work presents analytical solutions readily accessible for the dynamic analysis of MFS utilizing conventional rectangular pontoons subject to regular or irregular waves. Closed-form formulations utilizing linear wave theory proved capable in capturing the response amplitude operators (RAO) for sway, heave, and roll when compared against smoothed particle hydrodynamics (SPH) simulations for a typical MFS to which appropriate damping ratios were obtained. A parametric study was subsequently implemented to examine the contribution of building slenderness and superstructure-to-pontoon mass ratios on critical accelerations induced by different sea states. It was revealed that structural configurations beneficial to static stability may result in larger dynamic effects under wave excitation thus compromising occupant comfort delineated via various international standards. Ultimately, this paper represents a significant step towards the realization of MFS for urban expansion by providing structural engineers with an accessible methodology for the dynamic analysis of floating structures as a precursor to detailed computational modeling. •Performance of closed-form RAO solutions for MFS benchmarked against SPH.•Heave and roll damping ratio of 0.1 recommended for conservative assessment of MFS.•Building slenderness and building/pontoon mass ratio on human comfort explored.•Analytical procedure enables the preliminary design of MFS prior to CFD modeling.